2014
DOI: 10.1017/s0043933914000385
|View full text |Cite
|
Sign up to set email alerts
|

An overview of infectious bronchitis virus in chickens

Abstract: Infectious bronchitis virus (IBV) is one of the foremost causes of economic loss within the poultry industry. IBV is a commonly occurring, economically significant pathogen of commercial chicken. Economic consequences to the poultry industry comprise mortality, growth retardation and high condemnation rates in meat-type birds. In addition, decreased egg production, reduced internal and external egg quality, and reduced hatchability have been documented in layers and breeders affecting the performance of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 67 publications
4
46
0
Order By: Relevance
“…6). In breeder and laying hens QX-type causes delayed the onset of production, poor peak in egg production, a high percentage of falselayers and poor quality of eggs [20]. The QX prevalence obtained in the present study was 5% which could reflect the efficacy of vaccination [21].…”
Section: Discussionsupporting
confidence: 45%
“…6). In breeder and laying hens QX-type causes delayed the onset of production, poor peak in egg production, a high percentage of falselayers and poor quality of eggs [20]. The QX prevalence obtained in the present study was 5% which could reflect the efficacy of vaccination [21].…”
Section: Discussionsupporting
confidence: 45%
“…Since IB was first described by Schalk and Hawn in USA in 1931 [2], it has developed into one of the foremost causes of economic loss in the poultry industry, affecting the performance of both meat-type and egglaying chickens. IBV is an enveloped, non-segmented, single-stranded, positive-sense RNA virus, classified taxonomically as a member of genus Gammacoronavirus, family Coronaviridae [3]. Initially, this pathogen replicated primarily in the respiratory tract, causing a highly contagious respiratory disease characterized by nasal discharge, snicking, rales, and tracheal ciliostasis in chickens, but later reports demonstrated that it also replicated in many other epithelial surfaces, including enteric surfaces, oviducts, and kidneys [4].…”
Section: Introductionmentioning
confidence: 99%
“…Avian infectious bronchitis (IB) is an acute, highly contagious disease of all age groups of chicken and affects primarily the respiratory system with possible infection of renal and reproductive systems [1,2]. It is a disease of global importance and listed in the world organization for animal health (OIE) diseases.…”
Section: Introductionmentioning
confidence: 99%